Detection of antibiotic residues in edible tissue of slaughtered cows in Tabriz abattoir with FPT method - M.A Torbati; M Shamshiri; A Javadi (Bihdāsht-i Mavādd-i Ghaz̠āyī, 2011)
Antibiotic residues in food stuff and their transmission to the consumers have some consequences such as bacterial resistance, allergic reactions, intoxication, carcinogenic effects and disturbing of intestine natural flora of. Four-plate test is among microbiologic methods for detecting antibiotic residues in food stuff, which performs in four culture media with different pH values and test bacteria. In this study, 30 samples including gluteal muscle, diaphragm muscle, liver and kidney tissues obtained randomly from beef carcasses slaughtered in Tabriz abattoir were assayed. From total 30 kidney samples, every 30(100%) cases; among 30 liver samples, 28(93.33%); from 30 diaphragm samples, 22(73.33%) and from 30 gluteal muscle samples, 22(73.33%) cases were diagnosed as positive for  antibiotic residues. Results revealed that, the most antibiotic residues belonged to Penicilin and Macrolides groups (P